Campanhas eleitorais em um município amazônico em tempos de ditadura (Limoeiro do Ajuru, décadas de 1960-1980) - RODRIGUES, Eliton Rodrigues (2019)
The present study intends to understand how the participation of families related to large landowners in electoral campaigns, as well as the effect of this participation on the results of the elections in Limoeiro do Ajuru, State of Pará, during the 60 to 80 of the twentieth century. In this case, we are going to analyze six electoral processes, and the temporal cut is related to important historical events, such as the emancipation of the municipality in 1961, the first election in 1962 and 1982 as the inaugural landmark of the redemocratization period that brought an end to bipartisanship, new political groups, as well as greater political freedom. It is a study in which the political behavior of agents that formed the dominant local groups of traditional families who used land, property and economic power as instruments of political bargaining in the electoral process was observed, as well as describing the entanglements involving political discourses and actions in an Amazonian municipality.